1983
DOI: 10.1099/0022-1317-64-10-2317
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activities of Cloned Human Leukocyte Interferons against Herpes Simplex Virus Type 2 Infections of Mice

Abstract: SUMMARYHuman 0t-interferons (IFN-~s) made in bacteria were examined for antiviral activity against herpes simplex virus type 2 (HSV-2) infections of mouse L-cells in vitro, and acute cervicovaginal and lethal systemic HSV-2 infections of BALB/c mice. The recombinant DNA-derived hybrid interferon IFN-ctAD(Bgl) showed pronounced antiviral activity in vitro, exceeding the activity of either of the parental subtypes IFNetA and IFN-~tD and that of the other hybrids IFN-ctAD(Pvu) and IFN-ctDA(Bgl). A combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Our data suggest that there is a rapid and robust uptake of glucose by cells, within minutes of IFN-␤ treatment, consistent with meeting the energy demands of protein synthesis. Moreover, the nature of the biphasic response, whereby glucose uptake is initially increased, followed by a suppression, is in agreement with the paradigm of type I IFN-mediated antiproliferative effects (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71). Specifically, in uninfected cells, the early translation of antiviral proteins is followed by a progressive shutdown of protein synthesis that would disable cell growth and, upon infection, inhibit viral protein synthesis.…”
Section: Discussionsupporting
confidence: 78%
“…Our data suggest that there is a rapid and robust uptake of glucose by cells, within minutes of IFN-␤ treatment, consistent with meeting the energy demands of protein synthesis. Moreover, the nature of the biphasic response, whereby glucose uptake is initially increased, followed by a suppression, is in agreement with the paradigm of type I IFN-mediated antiproliferative effects (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71). Specifically, in uninfected cells, the early translation of antiviral proteins is followed by a progressive shutdown of protein synthesis that would disable cell growth and, upon infection, inhibit viral protein synthesis.…”
Section: Discussionsupporting
confidence: 78%
“…For example, interferon ax4 was only weakly effective as compared with other ao species in inhibiting both HSV and CMV. These results are in agreement with those of Fish et al (3,4), who showed that (10). It is of interest that both of the recombinant 1 interferons were more inhibitory to CMV than the ai species.…”
supporting
confidence: 93%
“…In all of these experiments, type I IFNs were shown to play a major role in the control of infection. Evidence for a role of type I IFNs in herpesvirus infections comes from studies on the administration IFNs (Rasmussen and Farley, 1975;Fish et al, 1983) and from work that demonstrates the importance of NK cells in clearance of infection (reviewed in Biron, 1997). Studies with EBV indicate that type I IFNs can downregulate proliferative responses to EBV in vitro (Aman and von Gabain, 1990), and evidence that the EBERs interfere with the function of IFN in vitro (Clarke et al, 1991) suggests that type I IFN activity is important in EBV infection.…”
Section: Discussionmentioning
confidence: 99%